A Stylistic Analysis of Adichie’s Half of A Yellow Sun - Ajadi, Rasaq A. (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
Language analysis has continued to benefit from a functional approach to its study and stylistics as a linguistic discipline is an approach to the functional interpretation of text. The purpose of this paper is to analyze peculiar linguistic features in relation to their functional values in Adichie’s Half of a Yellow Sun. The study employed such tools as graphology, morphology, and syntactic and lexico-semantics to examine the stylistic features in the text.The major findings of this study were: there is the use ofa non-structural linguistic element to indicate plot movement. Graphological elements such as spacing and asterisks were used to effect change in spatio-temporal contextjlanguage-character mapping is achieved via the use of such linguistic features as deviant word forms and expressions, compounding, etc. to reveal characters’ social, economic and educational levels. Also, loan words reveal the physical setting of the text. The syntactic and the lexico-sernantic features of the text foreground the themes entailed in the text. The subject matter of a writer informs his choice of words and expressions. The deployment oflanguage for experiential, interpersonal and textual functions depends largely on a language user’s effective competence in the language of communication and his sound control of the contextual variables ofher/his physical and linguistic contexts.